THE LATE XXth AND EARLY XXIst CENTURY WORLD LITERATURE AS A FACTOR IN SHAPING THE HISTORICAL MEMORY OF FUTURE TEACHERS - Trukhan, Oksana (Mountain School of Ukrainian Carpaty, 2022)
It is noted that fiction for various reasons loses its educational role among future teachers, and a certain educational potential of modern world literature is virtually unfamiliar to students. It has been proved that modern foreign literature, which actualizes Ukrainian issues, can become an effective means of educating spirituality, national-patriotic feelings and historical memory in future teachers. The interest of foreign authors in Ukraine, its historical past, raising of important issues of national identity, historical memory of Ukrainians is a stimulus for students to get acquainted with these literary works and to read them deeply. The object of study may be the novel "Chornobyl Prayer: A Chronicle of the Future" by the Nobel Prize-winning writer Svetlana Alexievich , as well as Taisa Bondar (the novel "In the Name of the Father and the Son"), Ivan Shamyakin (the novel "The Evil Star") , the American writer Irene Zabytko ("The Sky Unwashed"), representing diaspora literature, the novel by the Irish writer Darragh McKeon "All That is Solid Melts into Air", the literary work of the French illustrator Emmanuel Lepage "Springtime in Chernobyl", journalism of the American-English scholar Serhii Plokhy ("Chernobyl: The History of a Nuclear Catastrophe”) and others. These authors are thematically united by the Chernobyl accident, which they portray as a global catastrophe, as a national tragedy of Ukrainians, a huge psychological trauma for people. The writers emphasize that the Chernobyl explosion happened not only due to neglect of safety rules, problems with the construction of the reactor or staff errors, but also largely due to the socio-political system and the authoritarian regime of those times. Today, more than ever, these problems are urgent, especially taking into consideration the events that took place at the Chernobyl nuclear power plant as a result of the invasion of Russian troops. Unfortunately, there is a great threat of a repeat of this catastrophe. Therefore, the artistic and journalistic works of the “Chernobyl discourse” must be read carefully and in a new way, in order to prevent a recurrence of the Chernobyl disaster. The lessons of Chernobyl must not be forgotten and should never be allowed to happen today. Such issues are perhaps the most capable of shaping the national memory of youth, national consciousness and high spiritual values. Keywords: modern world literature, future teachers, historical memory, education, Chernobyl discourse, writers.